Vocationalisation of Healthcare Education: Driver of Growth (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Healthcare industry has become one of the prime sectors of the Indian economy, in generating revenue and employment. Health care education comprises of allied health staff such as radio technician, laboratory technicians, pharmacists, physiotherapist, homecaregivers for the elderly and many others. Many of these sectors are prime players to India's wellbeing and overall development, hence, healthcare vocational education must be taken in multiple ways. Vocational education is the need of the hour and especiallyneeded in skill-oriented industry such as Healthcare. We are required to raise the industry standards by having well-trained workforce in the field of healthcare. The demand and supply gap needs to be bridged and it can be achieved by having quality vocationalcourses. The Government is fully acquainted of the crucial role of vocational education and has already transformed in this area. This paper focuses on the significance of vocational education to meet the demands of the skilled workforce required by industryand how emerging healthcare industry has encouraged health professionals to join labour markets and ensure additional training and skill building. Increased availability and accessibility of healthcare services by population in general, enhanced investment inhealthcare care sector that will strengthen health system for dealing with pandemic situations like COVID-19 and any other epidemic/s. Also, skilled healthcare workers contribute to economic growth and overall economic well-being